In the Mind’s Eye: Exploring the Relationship Between Visual Mental Imagery and Stereotyping - Eisenstadt, Benjamin E.; Spagna, Alfredo; Stroessner, Steven J. (Personality and social psychology review, 2025)
Academic Abstract How do social stereotypes shape and reflect images formed in the mind’s eye? Visual mental imagery has long been assumed crucial in creating, maintaining, and perpetuating stereotypes and prejudice. Surprisingly, research in social cognition has only recently begun to explore the causal role of mental images in these phenomena. In contrast, cognitive neuroscience research on visual mental imagery (VMI) has explored the pivotal role of imagery in various consequential cognitive and behavioral phenomena. However, cognitive neuroscience has largely neglected how stereotypes influence mental imagery. This article provides a historical overview of the development of these two fields in terms of mental imagery and discusses recent advances at their intersection. Opportunities for additional integration are highlighted, and suggestions for furthering the dual study of stereotyping and mental imagery are provided. Public Abstract How can social stereotypes impact and mirror visual imagination? It has long been assumed that visual mental imagery plays a central role in forming, maintaining, and strengthening stereotypes and prejudice. Yet, until recently, there has been limited exploration within social psychology and cognitive neuroscience on the explicit connection between visual mental images and social stereotypes. We describe the historical progression of these fields concerning visual imagery and explore recent advancements that unite stereotyping and mental imagery research. Furthermore, we propose avenues for future research to deepen our understanding of how individuals utilize mental images in stereotyping and how mental imagery can modify stereotypes.